A pilot study on diagnosing laryngopharyngeal reflux disease by pharyngeal pH probe monitoring - Taner Torun, Mümtaz; Gümüşsoy, Murat; Çukurova, İbrahim; Burak Arslan, İ.; Kandoğan, Tolga (ENT Updates, 2013)
Objective: We aimed to evaluate (laryngopharyngeal reflux) LPR disease group and group with healthy volunteers and compare results obtained using Dx pH probe in the diagnosis of LPR disease. Methods: Fifty-seven LPR patients with typical scores of reflux symptom index (RSI) and reflux finding scoring (RFS) system and 20 healthy volunteers without laryngopharyngeal symptoms and physical examination findings were included in the study after excluding other concomitant diseases. All patients were requested to complete RSI and RFS forms. Healthy volunteers, with RSI 13 and RFS >7. Dx pH probes were applied to each group. Fisher’s exact test, Shapiro-Wilk test, T test and Mann-Whitney test were used for statistical analysis. A p value 0.05), despite a statistically significant intergroup difference (p<0.05). Conclusion: Dx pH probe was found to be an alternative to other methods commonly used in the diagnosis of LPR. When compared with RSI and RFS scores, Dx pH probes provided consistent and accurate data. Dx pH probe application can be an alternative to frequently used diagnostic methods for LPR.